(untitled) (Al-Academy, 2015)
In the midst of the public narrative film , we discussed the issue of dealing with the current narrative more specialized which its future dimension form shift and twist on the level of construction narrative film in some of its diverse and renewable trends in its two ways theoretical and practical and non-give important implications for the modes of operation of the renewable narrative structures and the fact that the cinema is an arts which always open to ideas in neighboring fields and this come naturally as a result of the continuing intellectual and knowledge sharing between cinema and other science . our current research has already begun to address the issue in a stream of consciousness narrative structure film based on all that the most important ideas and theories that have been made about the concept (stream of consciousness) which emanating mainly from the field of analytical psychology , and it should be noted that the term has been used narrative sense and early in the field of literature novelist and by the novelist and theorist ( William James ) and finally settled in the film practically …thus the current study (artistic and intellectual approach to the construction of the stream of consciousness in the film novelist) dealt four chapters have been search through them in the midst of this issue, the form of the first chapter of systematic research framework and which have been addressing the problem of research and emphasis on the importance of this study and its narrative studies of modern art film … In addition to the goals set by the researcher, the research has moved in the range of its theoretical part about all that is written about the stream of consciousness as a holistic approach and the narrative has privacy and intellectually based in distinct narrative speeches …In its application part the research has been sets in a model applied one representing the film (the boy) for reason that will mentioned later.In the second chapter, which came under the title (the theoretical framework) , research charted his way through access to the most important ideas and theories that have been made about the concept of stream of consciousness and what constitutes the basis and reference can be invoked in the analysis and to enter in to the subject and read it as systematic process and practical which based on the clear concept of stream of consciousness .. This research included three topics, first titled (stream of consciousness term and concept ) in which the researcher cleared the emergence of the term and distinguish it from what is Described Alsaiklogi stories… The second section was titled ( technical approach to stream of consciousness ) and it has been dealt with engaging narrative logic of the approach according to the stream of consciousness ..The third section came under the title (the construction of time in the stream of consciousness) to be an integral link and former two sections , and it was to clarify the nature of the contrary and the task by which the time can be constructed according to the approach of stream of consciousness .. In the third chapter , which came under the title ( research procedures ) were introduced to the methodology of research and search tool and the limits of research and sample neshat and the reasons for selecting the sample .. In the fourth chapter included ( research and the results of the most important conclusions ) that have been drawn from the search after neshat sample analysis followed by a list of sources approved by the research , and summary in English